Aetiology of bronchiectasis in adults: A systematic literature review. Issue 8 (19th June 2016) - Gao, Yong‐hua; Guan, Wei‐jie; Liu, Shao‐xia; Wang, Lei; Cui, Juan‐juan; Chen, Rong‐chang; Zhang, Guo‐jun
Abstract: While identifying the underlying aetiology is a key part of bronchiectasis management, the prevalence and impact of identifying the aetiologies on clinical management remain unclear. We aimed to determine the etiological spectrum of bronchiectasis, and how often etiological assessment could lead to the changes in patients' management. A comprehensive search was conducted using MEDLINE (via PubMed) and EMBASE for observational studies published before October 2015 reporting aetiologies in adults with bronchiectasis. Of the 8216 citations identified, 56 studies including 8608 adults with bronchiectasis were relevant for this systematic review. The crude prevalence for the identified aetiologies ranged from 18% to 95%, which possibly resulted from the differences in the geographic regions and diagnostic workup. Post‐infective (29.9%), immunodeficiency (5%), chronic obstructive pulmonary disease (3.9%), connective tissue disease (3.8%), ciliary dysfunction (2.5%), allergic bronchopulmonary aspergillosis (2.6%) were the most common aetiologies. In 1577 patients (18.3%), identifying the aetiologies led to changes in patient's management. Aetiologies varied considerably among different geographic regions ( P < 0.001). Intensive investigations of these aetiologies might help change patient's management and therefore should be incorporated into routine clinical practice.